Transparency in extractive industry commodities trading - Olle Östensson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The paper reviews the debate about transparency in extractive industry commodities trade. It examines the obstacles to improved transparency. A critical review of the experience with estimating losses from a lack of transparency concludes that many of the published estimates of losses from transfer mispricing and misinvoicing suffer from methodological deficiencies and appear to be exaggerations. The role of finance in extractive commodities trade is briefly discussed and it is noted that lending to companies owned by the state may affect the government's standing with donors and investors. The most important transparency and responsible sourcing initiatives are reviewed. The initiatives appear to have had some positive effect on public financial management, investment climate, and economic growth. The experience of government-initiated responsible sourcing, including for conflict minerals, concludes that initiatives must include all or almost all market participants and that the cost of due diligence be equitably shared. Finally, a number of recommendations are made.
Keywords: H26; K42; L71; L72; 330; transparency; commodity trading; extractive industries; conflict minerals; responsiblesourcing; transfer mispricing; misinvoicing